Automatización de envasadora de polvos horizontal tipo sachet para la industria farmacéutica (2024)
The development of this project shows the development of the automation of the marzio machine in the sachet type powder packaging process, located in the area of Packaging and Conditioning in the company Coaspharma, improving the productivity and efficiency of the equipment, changes and automations were implemented in its different systems such as the sealing system, advancement, cutting, foil unwinding and dosing, The aim is to minimise equipment stoppages due to adjustments and maintenance interventions, reducing the use of raw materials such as packaging and product resources, and interventions by production personnel due to issues related to the fine-tuning of the equipment, facilitating the relevant adjustments to the equipment in order to improve the quality of the finished product.